U.S. Army Physical Demands Study: Differences in Physical Fitness and Occupational Task Performance Between Trainees and Active Duty Soldiers. Issue 7 (July 2019) - Canino, Maria C.; Foulis, Stephen A.; Zambraski, Edward J.; Cohen, Bruce S.; Redmond, Jan E.; Hauret, Keith G.; Frykman, Peter N.; Sharp, Marilyn A.
Abstract : Abstract: Canino, MC, Foulis, SA, Zambraski, EJ, Cohen, BS, Redmond, JE, Hauret, KG, Frykman, PN, and Sharp, MA. U.S. Army Physical Demands Study: Differences in physical fitness and occupational task performance between trainees and active duty soldiers. J Strength Cond Res 33(7): 1864–1870, 2019—U.S. Army initial entry training (IET) is designed to prepare trainees for the military environment and subsequent training, including specific programs to increase physical fitness to perform job-specific tasks to the minimal acceptable performance standard (MAPS). The aim of this study was to compare physical fitness and occupational task performance of trainees at the end of IET to that of active duty soldiers. One hundred seventy-nine male combat arms trainees at the end of IET and 337 male combat arms active duty soldiers performed a sandbag carry (SBC), casualty drag (CD), and move under direct fire (MUF). Physical fitness was assessed using Army Physical Fitness Test scores. A questionnaire was administered to determine frequency of task performance. Active duty soldiers compared with trainees were older ( p < 0.01) and performed more push-ups ( p < 0.01) and sit-ups ( p < 0.01). Trainees performed the 2-mile run faster ( p < 0.01). Ninety-four percent of trainees and 99% of active duty soldiers performed the 3 tasks to the MAPSs. Active duty soldiers performed significantly faster on both the SBC ( p < 0.01) and CD ( p < 0.01) and reported a higher task frequency on the SBC ( p = 0.03) and CD ( p < 0.01). No difference in MUF performance ( p = 0.16) and task frequency ( p = 0.13) was detected. Initial entry training seems to provide sufficient physical training as most trainees were able to meet the MAPSs; however, performance differences were still apparent between trainees and active duty soldiers. Additional practice performing the physically demanding tasks may help maximize performance on the physically demanding job requirements.